2010
DOI: 10.5507/bp.2010.012
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Postoperative Nausea and Vomiting in Patients at a University Hospital. Where Are We Today?

Abstract: Aim.To determine the incidence of postoperative nausea and vomiting (PONV), identify risk factors, assess treatment and its effectiveness.Design. A prospective, observational, questionnaire-and interview-based study. Setting. Standard and intensive care units of the following university hospital departments: abdominal, thoracic and vascular surgery; gynecology; plastic and esthetic surgery; urology; and traumatology.Material and methods. Adult patients scheduled for elective surgery who gave informed consent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 26 publications
2
21
1
1
Order By: Relevance
“…In addition, there were no significant differences in the duration of surgery or recovery time in the three groups. A relationship between PONV and airway management was demonstrated by L. Doubravska [6] was highest after orotracheal intubation (18.8%), but lower with face mask (8.9%) or laryngeal mask (6.2%) placement. Kovac AL [7] and Gan TJ [8] observed that certain surgical like abdominal, laparoscopic, ophthalmic, gynaecological, neurological, plastic and aesthetic or middle ear surgery and strumectomy and anaesthetic management influencing PONV include premedication, type of anaesthesia, induction agents used, opioids, nasogastric suction, muscle relaxation reversal, anaesthesiologist's experience, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there were no significant differences in the duration of surgery or recovery time in the three groups. A relationship between PONV and airway management was demonstrated by L. Doubravska [6] was highest after orotracheal intubation (18.8%), but lower with face mask (8.9%) or laryngeal mask (6.2%) placement. Kovac AL [7] and Gan TJ [8] observed that certain surgical like abdominal, laparoscopic, ophthalmic, gynaecological, neurological, plastic and aesthetic or middle ear surgery and strumectomy and anaesthetic management influencing PONV include premedication, type of anaesthesia, induction agents used, opioids, nasogastric suction, muscle relaxation reversal, anaesthesiologist's experience, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PONV varies with many potential causes.This depends on involving anesthetic agents, the type of procedure, and patient factors. 2,3,6,10 Despite many other studies about PONV in the other regions, the descriptive data about the incidence of PONV in Dr. Hasan Sadikin General Hospital Bandung is still unknown. Considering the huge effects of PONV, this study was aimed to determine the incidence of PONV in Dr. Hasan Sadikin General Hospital Bandung.…”
Section: −5mentioning
confidence: 99%
“…According to the literature, the procedure on middle ear will stimulate vestibular afferent nerve that will stimulate the vomiting center. 7,8,10,11 Despite the high incidence of PONV in surgeries mentioned earlier, PONV was also common in patients with digestive surgery, and ortophaedic surgery. It has to be noted that the emetic center is stimulated by several visceral afferents including digestive tract, and manipulation in this area could activate gastrointestinal responses.…”
mentioning
confidence: 99%
See 2 more Smart Citations